Efektifitas Pengenalan Nilai-Nilai Karakter pada Anak Tunagrahita Ringan di SD Inklusi Melalui Game Interaktif - Wendri Wiratsiwi; Sumadi Sumadi (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
The introduction of character values in students is very important to equip them with good character and to be able to distinguish between good behavior and bad behavior. Character education itself has a main function, namely developing the basic potential of students, both in thinking and behaving in society and improving the nation's civilization that is competitive in world relations. Once the importance of character education in providing positive input for the progress of the nation, so it must be used as a basis for learning. No exception for children with mild mental retardation in inclusive elementary schools. This mild mentally retarded student requires repetition in learning as well as its application in a concrete and continuous manner. Therefore, this study aims to describe the effectiveness of implementing the introduction of character values for mild mentally retarded children through interactive games in inclusive elementary schools. This study uses qualitative research through descriptive methods with data collection techniques through observations and documentation studies. The subjects in the study were the  Teachers, and Students with the classification of children with mild mental retardation. The results showed that interactive games were effective enough to introduce character values for mild mentally retarded children in inclusive elementary schools.